Gender history across epistemologies - Gabaccia, Donna R., 1949-; Maynes, Mary Jo. (Chichester, West Sussex : John Wiley & Sons Inc., 2013)
This compilation of essays offers a broad range of innovative approaches to gender history, revealing how historians of gender are crossing disciplinary, methodological, and national boundaries to explore new opportunities for viewing gender as a category of historical analysis.
Introduction: Gender history across epistemologies / Donna R. Gabaccia and Mary Jo Maynes -- 1. Master narratives and the wall painting of the House of the Vettii, Pompeii / Beth Severy-Hoven -- 2.'More beautiful than words & pencil can express' : Barbara Bodichon's artistic career at the interface of her epistolary and visual self projections / Meritxell Simon-Martin -- 3. Public motherhood in West Africa as theory and practice / Lorelle Semley -- 4. Profiling the female emigrant : a method of linguistic inquiry for examining correspondence collections / Emma Moreton -- 5. Beyond constructivism? : gender, medicine and the early history of sperm analysis, Germany 1870-1900 / Christina Benninghaus -- 6.'I just express my views & leave them to work' : Olive Schreiner as a feminist protagonist in a masculine political landscape with figures / Liz Stanley and Helen Dampier -- 7. Gender without groups : confession, resistance and selfhood in the colonial archive / Christopher J. Lee -- 8. The power of renewable resources : Orlando's tactical engagement with the law of intestacy / Jamie L. McDaniel -- 9. The politics of gender concepts in genetics and hormone research in Germany, 1900-1940 / Helga Satzinger -- 10. The language of gender in lovers' correspondence, 1946-1949 / Sonia Cancian -- 11. Gender-bending in El Teatro Campesino (1968-1980) : a Mestiza epistemology of performance / Meredith Heller -- 12. Changing paradigms in migration studies : from men to women to gender / Nancy L. Green -- 13. Reconsidering categories of analysis : possibilities for feminist studies of conflict / Shirin Saeidi -- 14. An epistemology of collusion : Hijras, Kothis and the historical (dis)continuity of gender/sexual identities in Eastern India / Aniruddha Dutta.
'Originally published as Volume 24, Issue 3 of Gender & History.'
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Sex role -- History; Gender identity -- History; Women -- Identity -- History; Women -- History; Women -- Identity -- History; SOCIAL SCIENCE -- Gender Studies; Gender identity; Sex role; Women; Women -- Identity; Electronic books; History